Conditions : nine : a feminist magazine of writing by women with an emphasis on writing by lesbians - Gulerma, Isabela; Cochran, Jo; Carrillo, Jo (Baltimore : Conditions, 1983)
Fonds Suzan Daniel (FSD)
Engels
Monografie